Galanin (1-15) potentiates the antidepres-sant-like effects induced by Escitalopram in a rat model of depression - García-Durán, Laura; Flores-Burgess, Antonio; Cantero-García, Noelia; Puigcerver-Martínez, Araceli; Narváez-Bueno, José Ángel; Fuxe, Kjell; Santín-Núñez, Luis Javier; Millón-Peñuela, Carmelo; Díaz-Cabiale, Zaida (My University, 2021)
Selective 5-HT reuptake inhibitor antidepressants (SSRIs) are the first choice in major depressive disorder (MDD), but 50% of affected patients do not show improvement. Galanin(1-15) [GAL(1-15)] enhanced Fluoxetine antidepressant-like effects in an animal model of depression, the olfactory bulbectomy (OBX); however, further detailed analysis of GAL(1-15) effects as augmentation treatment in OBX rats are needed. In OBX rats, we analysed the effect of GAL(1–15) on Escitalopram (ESC)-mediated responses in behavioural tests related to despair. We studied whether GAL(1–15) effects involved 5-HT1AR using an in vivo model siRNA 5-HT1A knockdown rats. Moreover, we analysed by immunohistochemistry the expression of the immediate-early gene c-Fos (c-Fos IR) after the administration of GAL(1-15)+ESC in OBX rats in several nuclei involved in MDD. GAL(1-15) enhances the antidepressant-like effects of ESC, and the GALR2 antagonist M871 blocked GAL(1-15) mediated actions. The downregulation of 5-HT1AR by siRNA was sufficient to block GAL(1-15) effects. Our immunohistochemistry and principal component analysis (PCA) analysis suggest that two functional networks are involved in these effects; one includes the lateral (LHb) and medial (mHb) habenula, dorsal raphe (DR) and ventral tegmental area (VTA), and the other consists of the dentate gyrus (DG), and prefrontal cortex (PFC). The results open up the possibility of using GAL(1-15) in combination with SSRIs as a novel strategy for treating MDD.
Keywords: Depresión - Tratamiento; Galanin(1-15); Escitalopram; Depression; Olfactory bulbectomy rats